Periaqueductal gray neurons encode the sequential motor program in hunting behavior of mice - Hong Yu (Nature Portfolio, 2021)
Hunting behavior typically contains a sequential motor program, including search, chase, attack, and consumption. Here, the authors show that periaqueductal gray neuronal ensembles encode the sequential hunting motor program, which might provide a framework for decoding complex instinctive behaviors.